Internet And Civic Participation Among Malaysian University Students - Amirfarhangi, Farideh; Ahmad Ishak, Md Sidin; Nikfard, Pouria (Jurnal Pengajian Media Malaysia, 2015)
The internet no doubt plays a significant role in communication and transmission of information required for any form of participation in one’s social life. It has been argued that internet use can increase the extent of this transmission and can result in participation. Despite a significant worldwide decline in youth civic participation, few researchers investigate the inter-relationship between these two variables in a Malaysian context. The present quantitative-qualitative study was an attempt to investigate the role that the internet plays in civic participation among Malaysian university students, who, as informed citizens can play a significant role the achievement of Malaysia’s 2020 vision. Pearson correlation coefficient was used to analyse the data collected from 400 Malaysian university students. The findings revealed a wide use of internet among the students for both academic and nonacademic purposes; however, news and information did not significantly influence their motivation for civic activity participation whereas the opposite was true of the inter-relationship between internet advertisements and the civic indicators of engagement. Among other social and political reasons, this could be referred to as the lack of skill in analysing news media.This, in turn, requires a comprehensive programme of media literacy education at university level in this country.